High prevalence of Taenia solium taeniasis and cysticercosis in Tibetan schoolchildren in western Sichuan, China: a cross-sectional study. (December 2017) - Li, Tiaoying; Openshaw, John J; Chen, Xingwang; Medina, Alexis C; Felt, Stephen A; Zhou, Huan; Rozelle, Scott D; Luby, Stephen P
Abstract: Background: Cysticercosis, an infection caused by the larval stage of Taenia solium, is a serious but neglected disease in developing countries. Information about the prevalence of taeniasis, the gastrointestinal infestation with the adult tapeworm, and cysticercosis is lacking in China. In the current study, we aimed to understand the prevalence of T solium taeniasis and cysticercosis in children in a Tibetan region of western Sichuan. Methods: A cross-sectional study was conducted through cluster sampling in two Tibetan primary schools of Muli County, Liangshan Prefecture, in 2016. Sample collection in two schools was carried out in April and September, respectively, whereas treatment of taeniasis carriers was performed in December. Each student was questioned about a history of segment expulsion within the previous year by showing a segment photo, and also provided faecal and blood samples. All faecal samples were examined for presence of Taenia spp eggs by direct smear, and serum samples were tested for specific IgG antibodies to T solium cysticercus using an ELISA based on low-molecular-weight antigens of T solium cyst fluids. Treatment with pumpkin seeds combined with areca nut extract was provided to confirmed (stool-positive for Taenia spp eggs by microscopy) and suspected taeniasis carriers (reporting a history of segment expulsion within the previous year). All collected tapeworms following treatment were subject to morphology examination and genotyping by multiplex PCR. χ 2 test was used to compare the infection rate of T solium taeniasis and seroprevalence in different groups of students. Significance was set at p≤0·05. Informed consent was obtained and Institutional Review Board approval was received. Findings: A total of 636 students (mean sampling coverage 90%) were involved in the study, with a median age of 11 years (range 5–15). The overall prevalence of taeniasis due to all three endemic Taenia species ( T solium, T saginata, and T asiatica ) was 10·4% (95% CI 7·9–12·9). The prevalence of T solium taeniasis was 6·1% (95% CI 4·2–8·0). Eight (23%) of 35 T solium taeniasis carriers expelled multiple tapeworms (range 2–11), including concurrent infection with other Taenia species. The prevalence of T solium cysticercosis IgG antibodies was 12·9% (95% CI 10·4–15·4) in 619 tested students. Of 32 students with T solium taeniasis, 13 (41%) were seropositive, compared with 12% (63/529) in the group of students without T solium taeniasis (p<0·0001). When analysed separately, the two schools had similar T solium taeniasis prevalence and cysticercosis antibody seroprevalence. Interpretation: The current study suggests that the prevalence of T solium taeniasis and cysticercosis is high in schoolchildren in Tibetan rural areas of western Sichuan. Further studies to better understand transmission patterns and risk factors in poor-resource rural areas of western China are needed to aid further eradication efforts. Funding: Global Development and Poverty Initiative at Stanford University, Sichuan Provincial Department of Finance, and Science and Technology Department of Sichuan Province (2014SZ0151).